Optimization and experimental analysis of drilling process parameters in radial drilling machine for glass fiber/nano granite particle reinforced epoxy composites. (2022) - Ramesh, B.; Sathish Kumar, S.; Elsheikh, Ammar H.; Mayakannan, S.; Sivakumar, K.; Duraithilagar, S.
Abstract: Matrix cracking, fibre damage, increased hole surface roughness, delamination, circularity, and thermal deterioration, among other things, all occur throughout the drilling process, reducing hole quality. The most concerning of the unfavorable effects is delamination. Delamination can be reduced and hole quality improved by using the optimum cutting parameters and drill bit type. When drilling glass fiber/nano granite powder reinforced epoxy composites, the influence of drill bit coating material, drill bit speed, and drill bit feed rate on surface quality is investigated. The Taguchi L9 rotationally symmetric array is used to develop the experiments. As a result, to coincide radial drilling parameters of the process and response parameters, the statistical analysis of the experimental results is done using ANOVA. The results of the tests show that, high spindle speeds and a bronze oxide coated drill bit produce better hole quality and are also the most important factors influencing the drilled hole quality.